Project-based learning in Scottish prisons (UCL Press, 2014)
The article describes the development of a project-based approach to learning in seven Scottish prisons. It argues that the project-based approach is ideally suited to prison education due to its flexibility and ability to enrich the relatively narrow prison curriculum and create meaningful links with wider society, reducing the isolation of prisoners. The approach also empowers staff and encourages interdisciplinary working. The project-based approach is well placed to support and reinforce desistance-based practice in education and fits well with both the new Scottish Prison Service strategy, Unlocking Potential, Transforming Lives and with Scottish Government's education policy, Curriculum for Excellence.